Hubungan Tingkat Pengetahuan Ibu Hamil Tentang Anemia Dengan Kepatuhan Kunjungan Antenatal Care Di Kelurahan Panrannuangku: The Relationship of Pregnant Women's Knowledge Level About Anemia and Compliance with Antenatal Care Visits in Panrannuangku District - Mantasia, Mantasia; Sumarmi, Sumarmi; Kartini H, Anita; Dewi, Dewi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Antenatal care is a procedure that is routinely carried out by health workers to build good relationships in the service process for pregnant women for early detection, supervision during pregnancy and preparation for childbirth. One of the factors that is underutilized in antenatal care services is the low level of knowledge and understanding of pregnant women. The aim is to determine the relationship between knowledge of antenatal care and compliance with visits for pregnant women during pregnancy. The research objective is to determine the relationship between the level of knowledge of pregnant women about anemia and compliance with antenatal care visits in Panrannuangku sub-district in 2023. The research method uses a cross-sectional approach, sample selection using total sampling. Sample of 30 respondents. All data was collected by filling out a questionnaire that had been created by data processing researchers using Chi Square test analysis. Results: Respondents with good knowledge were 17 respondents (54.8%), 16 respondents (51.6%) had complete ANC visit compliance and 1 respondent (3.2%) did not comply with ANC visits. Respondents with sufficient knowledge were 9 respondents (29%) where 5 respondents (16.1%) had complete ANC visit compliance and 4 respondents (12.9%) did not comply with ANC visits, respondents with less knowledge were 5 respondents (16, 1%) where 1 respondent (3.2%) had complete ANC visit compliance and 4 respondents (12.9%) did not comply with ANC visits. The results of the statistical test α = 0.05 resulted in p = 0.003 < 0.05. Conclusion: There is a significant relationship between the level of knowledge of pregnant women about anemia and compliance with ANC visits.